Influence of different supplements and sugarcane (Saccharum officinarum L.) cultivars on intake, digestible variables and methane production of dairy heifers under tropical conditions - Pedreira, Marcio dos Santos; Berchelli, Telma Teresinha [UNESP]; Primavesi, Odo; de Oliveira, Simone Gisele; Frighetto, Rosa; de Lima, Magda Aparecida (Springer, 2012)
The sulphur hexafluoride (SF6) gas tracer method was used to measure methane (CH4) production of crossbred (3/4 Holstein x Zebu) dairy heifers fed two types of sugarcane (Saccharum officinarum L.; cultivar IAC-862480 (CC1) or cultivar IAC-873184 (CC2)) and supplemented with urea or concentrate. The study was performed at Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) Southeast Cattle, So Carlos, SP, Brazil, using a completely randomised design. Differences between treatments were significant for digestibility of dry matter, organic matter and energy. When animals were supplemented with urea differences between sugarcane cultivars did occur for NDF consumption, but not for daily methane production. This suggest that variation in chemical composition of sugarcane did not affect bovine ruminal CH4 emissions. Concentrate inclusion in animal diet increased digestible organic matter intake, improving the nutrient intake by animals, but did not reduce CH4 production expressed as a percentage of gross energy intake.
Keywords: Energetic efficiency; Greenhouse gases; Soluble carbohydrate; Sulphur hexafluoride